2017
DOI: 10.1007/s12640-017-9714-0
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of Kynurenic Acid, 3-Hydroxykynurenine, sIL-2R, IFN-α, and IL-4 with Clinical Symptoms During Acute Relapse of Schizophrenia

Abstract: Several lines of evidence suggest that up-regulation of immune response and alterations of kynurenine pathway function are involved in pathogenesis of schizophrenia. Correlations among clinical status (using PANNS, SANS and SAPS scales) and blood levels of kynurenic acid (KYNA), 3-hydroxykynurenine (3-HK) and levels of selected immunoactive molecules, soluble interleukin-2 receptor (sIL-2R), interferon-α (IFN-α) and IL-4 were analyzed in 51 chronic schizophrenia patients during acute relapse, after four weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 48 publications
5
24
1
1
Order By: Relevance
“…In line with previous studies in SZ and schizoaffective disorders [16,33,34], we found plasma KYNA to be significantly lower in patients with SSD compared to controls. As also noted by others, this result is inconsistent with findings in post-mortem brains [6][7][8]15] and CSF [9][10][11]23].…”
Section: Discussionsupporting
confidence: 93%
“…In line with previous studies in SZ and schizoaffective disorders [16,33,34], we found plasma KYNA to be significantly lower in patients with SSD compared to controls. As also noted by others, this result is inconsistent with findings in post-mortem brains [6][7][8]15] and CSF [9][10][11]23].…”
Section: Discussionsupporting
confidence: 93%
“…KA levels were found to be increased in their study, however this result may have been confounded by a gender imbalance in this study (69% male in patients vs. 44% in controls), considering KA levels are lower in females than males (33,34). Szymona et al (30) analyzed blood levels of KA and 3-HK in 51 chronic schizophrenia patients during acute relapse, after 4 weeks of therapy and at remission. KA levels were significantly lower in comparison with controls throughout the study, whereas 3-HK did not differ from controls at admission and during therapy but increased at remission and correlated negatively with the improvement of negative symptoms (SANS scores) at discharge-matching our findings for PANSS negative scale scores.…”
Section: Trait and State Markers Of Psychotic Illnessmentioning
confidence: 56%
“…Furthermore, subgroup analyses of a recent meta-analysis by Plitman et al of 13 studies in schizophrenia demonstrated that KA levels were increased centrally (cerebrospinal fluid and brain tissue, n = 7 studies) but not peripherally (n = 5 studies) (28). However, two studies of peripheral IDO pathway metabolites which have emerged since then suggest a relative decrease in KA even in the presence of a pro-inflammatory state (29,30). We therefore repeated this meta-analysis using the same methods, while adding the data of the two newer studies plus our own findings.…”
Section: Trait and State Markers Of Psychotic Illnessmentioning
confidence: 99%
“…In this study, we found that plasma KYNA levels were significantly higher in SCZ patients than in healthy controls, which is consistent with three previous studies. 23,31,32 In contrast, two studies reported a decrease in blood KYNA levels in untreated SCZ patients, 33,34 and two other studies reported no significant differences in blood KYNA levels between medicated SCZ patients and controls. 35,36 Several factors, such as differences in demographic data (sex, age), technical differences in measuring KYN metabolite levels, and differences in tested materials or antipsychotic treatments, may have an impact on blood KYNA levels, and lead to differences in study results.…”
Section: Discussionmentioning
confidence: 97%